A prospective randomized study of a dental appliance compared with uvulopalatopharyngoplasty in the treatment of obstructive sleep apnoea. - Wilhelmsson B; Tegelberg Å; Walker-Engström M; Ringqvist M; Andersson L; Krekmanov L; Ringqvist I (Acta Oto-Laryngologica, 1999)
The enthusiasm for uvulopalatopharyngoplasty (UPPP) in the treatment of obstructive sleep apnoea (OSA) has declined in recent years, partly because of a lower success rate over time and partly because of adverse effects. Reports on the beneficial effects of dental appliances exist, but only one prospective randomized study has been published comparing dental appliances with nasal continuous positive airway pressure (CPAP) treatment. No study has been published comparing dental appliance treatment with UPPP. Ninety-five male patients with confirmed OSA, subjective daytime sleepiness and an apnoea index (AI) >5 were randomized for subsequent treatment with either a dental appliance or UPPP. There were 49 patients in the dental appliance group and 46 in the UPPP group. Thirty-seven patients in the dental appliance group and 43 in the UPPP group completed the 12-month follow-up. The success rate (rate of patients with at least a 50% reduction in AI) for the dental appliance group was 95%, which was significantly higher (p<0.01) than the 70% success rate for the UPPP group. According to the criteria for OSA (apnoea index >=5 or apnoea/hypopnoea index >=10), 78% of the dental appliance group and 51% of the UPPP group were normalized after 12 months. The difference between the groups was significant (p<0.05). These findings suggest that the dental appliance technique is useful in the treatment of mild to moderate OSA.